Strategi Pengembangan Agribisnis Jambu Mete - Ihsan Ihsan; Natelda R. Timisela; Ester D. Leatemia (Hasanuddin University, 2023)
The purpose of this study was to determine the agribusiness system, income level, and development strategy. Determination of the sample of farmer respondents using Simple Random Sampling, with farmer respondents as many as 34 people. The results showed that the agribusiness system includes cultivation, production, downstream processing and supporting institutions. The average total income of cashew farmers per harvest season is Rp. 4,582,022 with an average land area of 1.33 ha. Based on the results of the SWOT analysis, it can be concluded that the total score of the IFE matrix in the development of cashew agribusiness in Bantea Village is 2.826693 and the EFE matrix is 2.725203.